Definitive chemoradiotherapy for clinical T4b esophageal cancer – Treatment outcomes, failure patterns, and prognostic factors. (April 2021) - Huang, Tzu-Ting; Li, Shau-Hsuan; Chen, Yen-Hao; Lu, Hung-I; Lo, Chien-Ming; Fang, Fu-Min; Chou, Shang-Yu; Chiu, Yi-Chun; Chou, Yeh-Pin; Wang, Yu-Ming
Highlights: Definitive chemoradiation is an effective treatment for cT4b esophageal cancer. Age, N-stage, tumor length, and baseline BMI are survival prognosticators. Clinical complete response after chemoradiation has better survival. Locoregional recurrence remains the major failure pattern. Salvage local treatment improves outcome after locoregional failure. Abstract: Purpose: The management of cT4b thoracic esophageal cancer (EC) is challenging. The optimal treatment remains unclear, and prospective or large-scale retrospective reports on treatment outcomes are lacking. The present study was conducted to investigate the treatment outcomes, failure patterns, treatment responses, and prognostic factors focusing on cT4b thoracic EC treated by definitive concurrent chemoradiotherapy (dCRT). Methods: A retrospective review of cT4b thoracic EC patients treated with curative intent dCRT at our institution between 2009 and 2017 was conducted. Survival analysis was calculated using the Kaplan-Meier method, and prognostic factors were examined by the Cox proportional hazards model. Results: A total of 95 cT4b EC patients were included, and the median survival was 11.4 months. The 1-year, 3-year, and 5-year survival rates were 49.4%, 22.2%, and 19.0%, respectively. Forty-six patients (48.4%) experienced locoregional failure, 3 patients (3.2%) developed distant metastasis, and 11 patients had synchronous locoregional and distant failure. The corresponding 1-year, 3-year, and 5-year locoregional failure rates were 62.6%, 74.5%, and 79.2%, respectively. The treatment response rate was 76.9%, and clinical complete response was achieved in 25.3% of patients. Multivariable analysis revealed that age ≤ 65 ( p = 0.003), pre-dCRT body mass index (BMI) > 21 ( p < 0.001), clinical N stage 0–1 ( p = 0.014), and tumor length ≤ 6 cm ( p = 0.026) were independent prognosticators for better survival. Conclusion: Our study revealed that long-term survival is achievable for cT4b EC patients treated by dCRT, with a 3-year survival rate of more than 20%. Locoregional recurrence was the most common failure pattern. Age, BMI, N stage, and tumor length were significant prognosticators for survival in this group of patients.